A framework to assist in the analysis of risks and rewards of adopting BIM for SMEs in the UK - Lam, Thep Thanh; Mahdjoubi, Lamine; Mason, Jim (Journal of Civil Engineering and Management, 2017)
Building information modelling (BIM) adoption amongst larger construction firms and innovators seems to be on the increase. However, there is evidence to suggest that small and medium sized enterprises (SMEs) are currently lagging behind and are losing out in winning publicly funded projects. Guidance and frameworks to assist SMEs to make an informed decision about BIM adoption are currently lacking. There has been no systematic effort to date to bring together the results of research in SMEs’ BIM adoption. Consequently, this paper seeks to bridge this gap and provide a conceptual framework to give a theoretical foundation to the study of brokering risks and rewards in the adoption of BIM for project delivery. This framework is comprehensive and includes trading off risks and rewards associated with several criteria, such as stage of involvement, project value, funding, and the procurement route chosen. The approach has been validated by a representative sample of BIM users and the findings of the validation are also presented. The findings of the framework validation reveal that early design stage, project size between £5 m and £50 m, private funding, and integrated project delivery procurement are the best opportunities that enable SMEs to maximise the benefits and minimise the risks, when adopting BIM.First published online: 15 May 2017